1977
DOI: 10.1007/bf02207821
|View full text |Cite
|
Sign up to set email alerts
|

A review of important concepts in the trophic organization of pelagic ecosystems

Abstract: The physical environment has an important influence on the size composition of primary producers in plankton communities. This effect is transmitted through the trophic structure by size selective feeding processes at each level. A pictorial representation of trophic organization in pelagic ecosystems is presented which illustrates the complex involvement of individual species in the food web and the dynamic nature of ecosystem development along alternate pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 37 publications
(30 reference statements)
1
33
0
1
Order By: Relevance
“…Historical events often cause switching to other directions (whi& is also a normal process in the pelagic environment: see e.g. Landry, 1977) or a step ba& to earlier stages. An improved theory of community organization, which is necessary for the derivation of models predicting natural and man-influenced behaviour of ecosystems, should consider the existence of both in the marine environment, i.e., multiple stable points and succession-like sequences leading to them.…”
Section: Theoretical Aspects and Conclusionmentioning
confidence: 99%
“…Historical events often cause switching to other directions (whi& is also a normal process in the pelagic environment: see e.g. Landry, 1977) or a step ba& to earlier stages. An improved theory of community organization, which is necessary for the derivation of models predicting natural and man-influenced behaviour of ecosystems, should consider the existence of both in the marine environment, i.e., multiple stable points and succession-like sequences leading to them.…”
Section: Theoretical Aspects and Conclusionmentioning
confidence: 99%
“…Such changes, when coupled with advective processes, may result in asynchronous distributions of larvae and their principle prey (Nelson et al 1977, Lasker 1978, Bailey 1981. Persistent turbulence may also influence zooplankton species composition and food chain length (Greve & Parsons 1977, Landry 1977) and turbulent events (e.g. storms) may dilute aggregations of microzooplankton (Lasker 1978, Lough 1984, Tilseth & Ellertsen 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial interpretation was that the increasing TTE with N to the left of the transition point was attributable to the increased consumption of P l by Z, and the associated shortening of the average length of the food chain (e.g. Ryther 1969, Landry 1977. However, as we shall demonstrate below, the actual explanation lies in the effects of saturating resource utilization.…”
Section: Phase-shift Responses and Trophic Efficiencymentioning
confidence: 95%
“…Previous studies have suggested that major changes in trophic efficiencies may arise with eutrophication via several mechanisms, including alterations in species composition (and attendant nutritional value) of phytoplankton and zooplankton (e.g. Landry 1977, Scavia et al 1988). In addition, there are numerous reports of eutrophication-induced degradation of habitat conditions in lakes (e.g.…”
Section: Concluding Commentsmentioning
confidence: 99%
See 1 more Smart Citation